Respiratory ATP cost and benefit of arbuscular mycorrhizal symbiosis with Nicotiana tabacum at different growth stages and under salinity - Del-Saz, Néstor Fernández (Journal of plant physiology, 2017)
Copyright © 2017 Elsevier GmbH. All rights reserved.